Modulation of immune cell function, IDO expression and kynurenine production by the quorum sensor 2-heptyl-3-hydroxy-4-quinolone (PQS) - Ogbechi, Joy; Huang, Yi-Shu; Clanchy, Felix I. L.; Pantazi, Eirini; Topping, Louise M.; Darlington, L. Gail; Williams, Richard O.; Stone, Trevor W. (Frontiers in Immunology, 2022)
Many invasive micro-organisms produce ‘quorum sensor’ molecules which regulate colony expansion and may modulate host immune responses. We have examined the ability of Pseudomonas Quorum Sensor (PQS) to influence cytokine expression under conditions of inflammatory stress. The administration of PQS in vivo to mice with collagen-induced arthritis (CIA) increased the severity of disease. Blood and inflamed paws from treated mice had fewer regulatory T cells (Tregs) but normal Th17 cells. However, treatment of antigen-stimulated lymph node cells from collagen-immunised mice with PQS (1 M) in vitro inhibited the differentiation of IFNγ+ cells, with less effect on Th17 cells and no change in CD4+FoxP3+Tregs. PQS also inhibited T cell activation by anti-CD3/anti-CD28 antibodies. PQS reduced murine macrophage polarisation and inhibited expression of IL1B and IL6 genes in murine macrophages and human THP-1 cells. TNF gene expression was inhibited in THP-1 cells but not murine macrophages, while LPS-induced TNF protein release was increased by high PQS concentrations. PQS is known to have iron scavenging activity and its suppression of cytokine release was prevented by iron. Unexpectedly, PQS depressed the expression of indoleamine-2, 3-dioxygenase (IDO1 and IDO2) in macrophages and inhibited IDO1 enzyme activity indicated by reduced generation of kynurenine. This is consistent with evidence that IDO1 inhibition or deletion exacerbates arthritis, while kynurenine reduces its severity. The results suggest that low concentrations of PQS in the early stages of infection could account for the increased severity of autoimmune arthritis by suppressing IDO expression and Treg generation leading to a pro-inflammatory state.